Uncovering cell type-specific phenotypes using a novel human in vitro model of transthyretin amyloid cardiomyopathy - Jiabin Qin; Qiangbing Yang; Asier Ullate-Agote; Vasco Sampaio-Pinto; Laura Florit; Inge Dokter; Chrysoula Mathioudaki; Lotte Middelberg; Pilar Montero-Calle; Paula Aguirre-Ruiz; Joana de las Heras Rojo; Zhiyong Lei; et al. (Stem Cell Research & Therapy)
Abstract Background Transthyretin amyloid cardiomyopathy (ATTR-CM) is characterized by the misfolding of transthyretin (TTR), fibrillogenesis, and progressive amyloid fibril deposition in the myocardium, leading to cardiac dysfunction with dismal prognosis. In ATTR-CM, either destabilizing mutations (variant TTR, ATTRv) or ageing-associated processes (wild-type TTR, ATTRwt) lead to the formation of TTR amyloid fibrils. Due to a lack of representative disease models, ATTR-CM disease mechanisms are largely unknown, thereby limiting disease understanding and therapeutic discovery. Methods and results Here, we report a novel in vitro ATTR-CM model which uncovers cell type-specific disease phenotypes by exposing the three major human cardiac cell types to TTR fibrils, thereby providing novel insights into the cellular mechanisms of ATTR-CM disease. Human recombinant TTR proteins (WT, V122I, V30M) and respective fibrils were generated and characterized using Thioflavin T, Amytracker, Congo red and dot blot analyses. Seeding human induced pluripotent stem cell-derived-cardiomyocytes (hiPSC-CMs) and endothelial cells (ECs) on TTR fibrils resulted in reduced cell viability. Confocal microscopy revealed extracellular localization of TTR fibrils to hiPSC-CMs, leading to sarcomere disruption, altered calcium handling and disrupted electromechanical coupling, while ECs showed a reduced migration capacity with aberrant cell morphology. hiPSC-fibroblasts (hiPSC-FBs) were largely unaffected by TTR fibrils, presenting normal viability, but showing enhanced localization with TTR fibrils. Conclusions Our model shows that WT and variant TTR fibrils lead to cell type-specific phenotypes, providing novel insights into the underlying cellular disease mechanisms of ATTR-CM, thereby facilitating the identification of novel therapeutic targets and biomarkers.